In vitro anthelmintic activity of Piper betle L. (Sireh) leaves extract on gastrointestinal helminths obtained from goats - Mohammad, Mardhiah; Mat Yusof, Afzan; Mohd Azlan, Mawaddah (2018)
The livestock industry such as goat farming has been providing farmers with the steady income. However, mismanagement and poor welfare render animals particularly susceptible to parasites and diseases thus making demand-supply chains a challenged. The goats are infected by intestinal helminths and conditions worsened when they showed signs of resistance towards the majority of anthelmintic drugs commercially available. Other than improved husbandry, alternative treatments of affordable and easily accessible local plants are essential to be sought. Thus, the research is aimed to evaluate in vitro anthelmintic effect of Piper betle L. leaves extract on gastrointestinal helminths obtained from goats’ faecal samples and explores the potential of Piper betle L. as treatments. First, the occurrence of gastrointestinal helminths from 120 samples collected from 3 different goat farms in Kuantan, Pahang were determined using the microscope. These goats had also undergone physical screening of infectious states. Then, real-time PCR and high-resolution melt assay that confirmed the species of helminths was established. Next, the methanol extraction of Piper betle L. leaves was screened for their phytochemical compounds using light- and gas-chromatography-mass spectrometry (LCMS) and (GCMS) respectively. Finally, the anthelmintic effect of the extract on predominant species was determined by egg hatch assay (EHA) and larva paralysis assay (LPA). This study has identified 74.17% (89/120) samples of positive gastrointestinal helminths and discovered Haemonchus contortus a predominant among the six different species found. The study also revealed multiple infections of gastrointestinal helminths in a sample. The diagnosis of Helminthiasis is problematic and often unrecognized in the animal. The diagnosis is usually suspected on the basis of physical inspection for the treatment group. Nevertheless, this study has found no direct relationship between physical screening and microscopic observation. With perfect body score, the goats are actually severely infected when their faecal samples were studied. Thus, the demonstration of Helminthiasis using microscopic and molecular assay not only confirms the occurrence but also the species. Both GCMS and LCMS have revealed ‘Phenols’ as majority bioactive compound that is responsible for the anthelmintic components. LCMS has found many more compounds with different possible uses that could be utilized further. Piper betle L. has effectively eradicated Haemonchus contortus eggs and larvae. Both assays demonstrated that all tested concentration induced anthelmintic activity where 100% mortality was achieved at the concentration of 5.0 mg/ml within 24 hours for EHA and concentration of 7.5 mg/ml within 12 hours for LPA. In conclusions, Piper betle L. leaves that possess the anthelmintic properties were successfully shown of capable for acting as anthelmintic agent on the predominant species of gastrointestinal helminths from goats. Nevertheless, these strategies represent possible therapeutic treatment in the future.